Розробка рідкокристалічних чутливих елементів оптичних сенсорів для визначення концентрації парів ацетону та спиртів - Качурак , Юрій Михайлович (Національний університет «Львівська політехніка», 2024)
The thesis is devoted to the development of liquid crystal sensitive elements of optical sensors based on nematic LC E7 and cholesteric LC CB15 as a detector of acetone and alcohols, to the study of cholesteric-nematic liquid crystal mixtures for interaction with vapors of harmful organic substances, and manifestations of the blue phase during such interaction. The first chapter is devoted to the study of the latest trends in the field of optical sensors development where liquid crystals are the active medium. Research on the topic of the blue phase (BP) of liquid crystals, methods of its stabilization, and the use of this phenomenon in optical sensors is also considered. Modern approaches to the development of liquid crystal optical sensors using the blue phase effect are considered.
Development of liquid crystal sensitive elements of optical sensors for determining the concentration of acetone vapors and alcohols
Keywords: нематичний рідкий кристал, холестеричний рідкий кристал, рідкий кристал, хіральна домішка, оптичний сенсор, сенсор, чутливий елемент, температурна залежність, блакитна фаза, фазовий перехід, ацетон, етанол, метанол, спектр поглинання, nematic liquid crystal, cholesteric liquid crystal, liquid crystal, chiral dopant, optical sensor, sensor, sensitive element, temperature dependence, blue phase, phase transition, acetone, ethanol, methanol, absorption spectrum; 621.382.592